1999
DOI: 10.1002/(sici)1096-911x(199904)32:4<272::aid-mpo6>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Osteopenia in young adult survivors of childhood cancer

Abstract: Background Improved survival of children with malignant diseases is in part due to the application of intensive, multimodality therapies, including radiotherapy, surgery, glucocorticoids, and cytotoxic agents. Such interventions have the potential to induce complex hormonal, metabolic and nutritional effects that may interfere with skeletal mass acquisition during childhood and adolescence: it is possible that such childhood cancer survivors may therefore reach adulthood with diminished peak bone mass and be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 34 publications
1
38
0
3
Order By: Relevance
“…Because MTX is utilized in the treatment of childhood cancers, the present findings suggest that its effects on growing bones are complex and in need of further study. [36][37][38][39][40][41][42][43] While the clinical risk factors are multifactorial, specific chemotherapeutic agents, including high-dose MTX, ifosfamide, and bleomycin, have been implicated in causing bone loss. [43][44][45][46] By contrast, low-dose MTX in rats of age similar to ours (6 weeks) did not have a significant reduction in lumbar or femoral BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Because MTX is utilized in the treatment of childhood cancers, the present findings suggest that its effects on growing bones are complex and in need of further study. [36][37][38][39][40][41][42][43] While the clinical risk factors are multifactorial, specific chemotherapeutic agents, including high-dose MTX, ifosfamide, and bleomycin, have been implicated in causing bone loss. [43][44][45][46] By contrast, low-dose MTX in rats of age similar to ours (6 weeks) did not have a significant reduction in lumbar or femoral BMD.…”
Section: Discussionmentioning
confidence: 99%
“…If decreased bone mineralization is detected early, factors that might contribute to the low value should be recognized and if possible treated. Few patients with bone tumors have been included in previous studies of bone mass after childhood cancer (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, decreased bone mineralization has been demonstrated in long-term survivors of childhood acute lymphoblastic leukemia (2,5,6) and in children with a malignancy at completion of their chemotherapy (7)(8)(9). However, recent studies are controversial with respect to bone mass status in this group of patients (10), and few studies have included patients with bone tumors (11,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outra hipótese seria a perda aguda da DMO pela irradiação per se (39). Quimioterapia, incluindo o uso de corticosteróides e metotrexate, deficiências de hormônio do crescimento, de esteróides sexuais e de hormônio tireoidiano, além de deficiência nutricional, são outros fatores que podem estar envolvidos na patogênese da osteopenia (40).…”
Section: Distúrbios óSteo-metabólicosunclassified